PENGARUH DEPO MEDROXY PROGESTERON ACETATE (DMPA) TERHADAP GANGGUAN MENSTRUASI AMENOREA SEKUNDER PADA AKSEPTOR KB SUNTIK 3 BULAN DI WILAYAH KERJA PUSKESMAS KUTA ALAM KOTA BANDA ACEH TAHUN 2025 - Cut Efriana; Putri Kurniawati; Opiana Bako (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2025)
The use of injectable contraception is higher than other contraceptives, but the dropout rate among injectable contraceptive users is the second highest after the pill, at 24.7%. Changes in menstrual patterns or menstrual irregularities are the main factors causing dropout among injectable contraceptive users. This dropout can lead to an increase in the population, which will impact welfare, education quality, development, and health, and will also reduce the quality of life in a country. The purpose of this study was to determine the effect of depot medroxyprogesterone acetate on menstrual disorders and secondary amenorrhea among injectable contraceptive users in the Kuta Alam Community Health Center, Banda Aceh City, in 2025.This analytical study used a cross-sectional approach with purposive sampling, with a sample size of 54 participants. The study was conducted from August 3 to 14, 2025, with univariate and bivariate analyses using the Chi-square test. The results of the study showed that of the 33 respondents who had used DMPA for more than 1 year, the majority (27 respondents) experienced secondary amenorrhea, while of the 21 respondents who had used DMPA for less than 1 year, the majority (12 respondents) did not experience secondary amenorrhea. Based on the results of the Chi-Square test, the p-value was 0.008, indicating a relationship between DMPA use and secondary amenorrhea. Therefore, the hypothesis in this study was accepted (Ha). The conclusion of this study is that DMPA use has an effect on secondary amenorrhea. It is hoped that respondents will be able to choose contraception that suits their needs and increase their knowledge about the types of contraception and the side effects of each type by seeking information from various sources, especially health workers.